Customer and Employee Service Quality Management in the Airline Industry - Petchi, Cessie Sylvia (2003)
Fierce competition has raised standards leading customers to expect higher standards of service, and customers are Ideal for appraising how well employees have provided quality service because they interact directly with the employees. Quality of service in the airline also depends greatly on the quality of the employees, as dissatisfied employees would not perform a service at the required level, and this would affect the service delivery This study examined the customers' perceptions and expectations of service quality, and the service-performance gap that measures the employees' Job satisfaction in Singapore Airlines (SIA) and Malaysia Airlines (MAS), to reveal the status of the level of service quality as perceived by their customers (customers' Satisfaction) as well as the level of employees job satisfaction in each company The SERVQUAL questionnaire comprising of five major service quality dimensions (tangibility, reliability, responsiveness, assurance,and empathy) was used to measure the customers' perceptions of service quality, and a total or 200 customers from each airline company were approached. The employees' perceptions of job satisfaction were measured through a service quality questionnaire developed by Parasuraman et al., (1998), that addresses the seven key contributing factors (teamwork, employee job-fit, technology job-fit, perceived control, supervisory control systems, role conflict, and role ambiguity) that affects the job performance. The total population of the employees of SIA (60 employees), and 83 employees from MAS answered the job satisfaction questionnaires.